2020
DOI: 10.1080/02813432.2020.1843942
|View full text |Cite
|
Sign up to set email alerts
|

Is C-reactive protein associated with influenza A or B in primary care patients with influenza-like illness? A cross-sectional study

Abstract: Objective: Identifying influenza A or B as cause of influenza-like illness (ILI) is a challenge due to non-specific symptoms. An accurate, cheap and easy to use biomarker might enhance targeting influenza-specific management in primary care. The aim of this study was to investigate if Creactive protein (CRP) is associated with influenza A or B, confirmed with PCR testing, in patients presenting with ILI. Design: Cross-sectional study. Setting: Primary care in Lithuania, Norway and Sweden. Subjects: A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Additional patient characteristics and influenza aetiology results are described by Rystedt et al. [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additional patient characteristics and influenza aetiology results are described by Rystedt et al. [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…This secondary analysis used the 277 patients recruited from 30 primary care practices in Sweden, Lithuania and Norway where CRP was measured upon inclusion. This was the same subset as used in a study investigating the association of CRP with influenza A or B infection in patients with ILI [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been previously established, however, that the majority of viral infections we are likely to encounter will rarely raise CRP >30 mg/L, and a CRP of >30 mg/L during a viral illness such as influenza would typically indicate progression of disease and risk of viral pneumonia. 41 Further elevations raise the possibility of severe inflammation, a bacterial or other invasive infection. 42 Additionally, imaging studies have consistently demonstrated that even a modest CRP rise is associated with infiltrative changes on CT prior to respiratory symptoms.…”
Section: Methodsmentioning
confidence: 99%